The artist in the "inverted" world: the peculiarities of the transitional artistic thinking in the drama “My soul with a scar on my knee” by Yaroslav Vereshchak (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article is devoted to the typological characteristics of the metadram. Investigated here are the forming factors of metadiscourse and the reception of theater's theater's drams, that is «double scene», creation of the image of the artist and his modern sight. The article summarizes the dram of Yaroslav Vereshchak, «My Soul with Scar on the Knee» the functions of art, its ability to reflect complex historical reality and crisis modernity.
Keywords: autobiographism; intention; metadiscourse; typological; characteristics; autoreflection of the literature